Navigating Complex Implementation Contexts: Overcoming Barriers and Achieving Outcomes in a National Initiative to Scale Out Housing First in Canada. Issue 1 (14th August 2018) - Macnaughton, Eric; Nelson, Geoffrey; Worton, S. Kathleen; Tsemberis, Sam; Stergiopoulos, Vicky; Aubry, Tim; Hasford, Julian; Distasio, Jino; Goering, Paula
Highlights: Housing First can be implemented beyond demonstration sites without new resources. Using an intentional implementation strategy communities implemented high‐fidelity programs. One key implementation challenge was accessing affordable housing and housing subsidies. By helping develop housing specialists and reflective practice, the TTA facilitated effective implementation. Abstract: The scaling out of Housing First (HF) programs was examined in six Canadian communities, in which a multi‐component HF training and technical assistance (TTA) was provided. Three research questions were addressed: (a) What were the outcomes of the TTA in terms of the development of new, sustained, or enhanced programs, and fidelity to the HF model? (b) How did the TTA contribute to implementation and fidelity? and (c) What contextual factors facilitated or challenged implementation and fidelity? A total of 14 new HF programs were created, and nine HF programs were sustained or enhanced. Fidelity assessments for 10 HF programs revealed an average score of 3.3/4, which compares favorably with other HF programs during early implementation. The TTA influenced fidelity by addressing misconceptions about the model, encouraging team‐based practice, and facilitating case‐based dialogue on site specific implementation challenges. The findings were discussed in terms of the importance of TTA for enhancing the capacities of the HF service delivery system—practitioners, teams, and communities—while respecting complex community contexts, including differences in policy climate across sites. Policy climate surrounding accessibility of housing subsidies, and use of Assertive Community Treatment teams (vs. Intensive Case Management) were two key implementation issues.